2014
DOI: 10.1890/13-0620.1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of energetic equivalence in forest soil invertebrates

Abstract: Ecological communities consist of small abundant and large non-abundant species. The energetic equivalence rule is an often-observed pattern that could be explained by equal energy usage among abundant small organisms and non-abundant large organisms. To generate this pattern, metabolism (as an indicator of individual energy use) and abundance have to scale inversely with body mass, and cancel each other out. In contrast, the pattern referred to as biomass equivalence states that the biomass of all species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
81
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(92 citation statements)
references
References 54 publications
10
81
1
Order By: Relevance
“…Lumbricidae were extracted separately in situ with a mustard solution (area = 0.25 m 2 ). Soil fauna was determined to the species level, average weight per species was determined after drying at 60 • C and mass-length regressions and population biomass in mg dry weight m −2 was calculated as detailed in Ehnes et al (2014). For statistical analysis, soil fauna species were aggregated to the functional groups macro detritivores, including the taxonomic groups Coleoptera, Diplopoda, Isopoda, Lumbricidae, and Symphyla, and meso detritivores, including Collembola and Oribatida.…”
Section: Forest and Vegetation Properties Arthropod Biomass And Orgamentioning
confidence: 99%
“…Lumbricidae were extracted separately in situ with a mustard solution (area = 0.25 m 2 ). Soil fauna was determined to the species level, average weight per species was determined after drying at 60 • C and mass-length regressions and population biomass in mg dry weight m −2 was calculated as detailed in Ehnes et al (2014). For statistical analysis, soil fauna species were aggregated to the functional groups macro detritivores, including the taxonomic groups Coleoptera, Diplopoda, Isopoda, Lumbricidae, and Symphyla, and meso detritivores, including Collembola and Oribatida.…”
Section: Forest and Vegetation Properties Arthropod Biomass And Orgamentioning
confidence: 99%
“…First, we investigate the biodiversity value of jungle rubber, conventional rubber and secondary forest compared with oil palm agriculture by comparing observed species richness, density and biomass of litter-associated macroinvertebrate communities across these systems. Second, as a multitrophic measure of the rate of ecosystem processes carried out by these communities, we calculate total solid fresh mass energy flux in a system by incorporating community metabolism27, resource-specific assimilation efficiencies and biomass loss to predation18 into whole-community energy flux equations (Fig. 1).…”
mentioning
confidence: 99%
“…This hypothesis is supported by Ehnes et al (2014), who found that phylogenetic groups, more than the effect of land-use type, affected the allometric scaling. This means that there is a trade-off between being able to study and visualize energetic paths of the entire soil food web and keeping the resolution that can be obtained by studying single soil taxonomic groups.…”
Section: Body Size and Allometric Scalingmentioning
confidence: 79%
“…Finally, it has been suggested by Meehan et al (2006) and Ehnes et al (2014) that allometry could be sensitive to the different estimation techniques required for different taxa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation